Respostas
respondido por:
2
Ola Marcele
x + y = 5
x - y = 1
some
2x = 6
x = 3
3 + y = 5
y = 5 - 3 = 2
.
x + y = 5
x - y = 1
some
2x = 6
x = 3
3 + y = 5
y = 5 - 3 = 2
.
respondido por:
3
isolando o x > x=5-y
5-y-y=1
-2y+5-1=0
-2y+4=0
Delta= (-2²) -4*0*4
Delta= 4-4
delta=0
X= -(-2)+ou-0 / 2
X=4+ou-0/2
X=2, -2
logo >
Y=2
X=5-2
X=3
S=(3,2)
5-y-y=1
-2y+5-1=0
-2y+4=0
Delta= (-2²) -4*0*4
Delta= 4-4
delta=0
X= -(-2)+ou-0 / 2
X=4+ou-0/2
X=2, -2
logo >
Y=2
X=5-2
X=3
S=(3,2)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás